8C.05: EPOXYEICOSATRIENOIC ACIDS ARE INCREASED IN PLACENTAS OF PREECLAMPTIC PREGNANCIES. (June 2015) - Vedove, F. Dalle; Fava, C.; Jiang, H.; Zanconato, G.; Quilley, J.; Brunelli, M.; Vattemi, G.; Minuz, P.
Abstract : Objective: Plasma concentration of epoxyeicosatrienoic acids (EETs) derived from cytochrome P450 (CYP)-dependent metabolism of arachidonic acid is increased in women with preeclampsia (PE) as compared to normal pregnancy (N), and is even higher in fetal plasma (Herse et al. Circulation 2012, Jiang et al. Am J Hypertens 2013). We hypothesized that differences in EET synthesis or metabolism in the feto-placental unit underlie the observed differences in circulating EETs. Design and method: To evaluate EETs generation as well the expression of the relavant CYP isoforms and of the metabolizing enzyme soluble epoxide hydrolase (sEH), biopsies of placenta were collected from 19 N and 10 PE at the time of surgical delivery. EETs were extracted from tissue homogenates and analyzed by LCMS. Results: Both cis- and trans- EETs were detected in the placenta in PE and N, with similar mean ratios. Concentration of total EETs was higher in the placenta in PE compared to N (2.37 ± 1.42 ng/mg vs 1.20 ± 0.72 ng/mg, Mean ± SD, P < 0.01), especially the 5, 6-, 8, 9- and 11, 12-EETs, measured in a subgroup of tissue samples (N = 10, PE = 5), were elevated. By immunohistochemistry, CYP2C8 was not detectable, CYP4A11 showed weak positivity in the mesenchimal axis of some villi (up to 50%) and scattered signal in the others. Also CYP2J2 was detectable in mesenchimal elements of placentas (scattered in 10–40% of villi, up to 50%). sEH showed weak signal in 1–3 cells for each villous, with a regular pattern distribution. CYP2C8, CYP4A11 and CYP2J2 were not detectable in umbilical cord. Western blotting analysis of placenta homogenates revealed a higher expression of sEH in N with respect to PE (3.9 ± 0.9 vs 0.8 ± 0.4 sEH relative expression, P < 0.05). Conclusions: In conclusion, along with the enzymes implicated in their biosynthesis, significant amounts of EETs were found in the placenta and the umbilical cord. Reduced expression of sEH in PE may contribute to increased EET in the placenta. Altered synthesis of EETs occurs in the placenta, reinforcing the hypothesis of their pathogenetic role in PE.